2005
DOI: 10.1002/qua.20391
|View full text |Cite
|
Sign up to set email alerts
|

Essential amino acids interacting with flavonoids: A theoretical approach

Abstract: ABSTRACT:The interaction of two flavonoid species (resorcinolic and fluoroglucinolic) with the 20 essential amino acids was studied by the multiple minima hypersurface (MMH) procedures, through the AM1 and PM3 semiempirical methods. Remarkable thermodynamic data related to the properties of the molecular association of these compounds were obtained, which will be of great utility for future investigations concerning the interaction of flavonoids with proteins. These results are compared with experimental and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The MMH methodology usually hinges on semiempirical methods [20][21][22][23][24][25][36][37][38] (ΔEASSOC) from now [25]. A Boltzmann distribution is used to calculate the thermally averaged state of the typical macroscopic system at room temperature (298.15 K).…”
Section: Multiple Minima Hypersurfaces (Mmh) Calculationsmentioning
confidence: 99%
“…The MMH methodology usually hinges on semiempirical methods [20][21][22][23][24][25][36][37][38] (ΔEASSOC) from now [25]. A Boltzmann distribution is used to calculate the thermally averaged state of the typical macroscopic system at room temperature (298.15 K).…”
Section: Multiple Minima Hypersurfaces (Mmh) Calculationsmentioning
confidence: 99%
“…Multiple Minima Hypersurface (MMH) methodology, which validity for the study of molecular associations and for conformational analysis has been widely demonstrated by some of the co-authors, [30][31][32][33][34][35][36][37][38] was employed for random generation and optimization at semiempirical level of theory of α−α'Py n SiOH (n = 2,3). Most stable structures were DFT-refined for conformational analysis.…”
Section: Introductionmentioning
confidence: 99%
“…More structures only add redundant structures and rarely a change in the statistically averaged internal energy. It has also been published earlier 16, 19, 26.…”
Section: Systems and Computational Detailsmentioning
confidence: 84%
“…The multiple minima hypersurfaces (MMH) approach estimate association energies of the molecular ground states combining semiempirical QM method and statistical thermodynamics formulae 16, 17. Applications to several objects of this method are being recently published 18–20, including hydration clusters of silicates, drugs, and water 16, 17, 20.…”
Section: Introductionmentioning
confidence: 99%